The double originality of rawls (1994)
This article is a critical introduction to one of the principalsystematic answers on the question of justice in contemporary thought: Rawls' egalitarian liberalismo For Van Parijs, political philosophy must have relevance, i.e. it must respond to the problems of the world without ignoring the human spirit. Therefore, he says that we need to study the sources of the solidarity schools of thought -marxism, utilitarianism and egalitarian liberalism- to answer thechallenge of libertarianism, the philosophical spearhead of neoliberal thinking. The text does not restrict itself to interpretation: it goes deeply into each argument, contrasting and criticizing the various hypotheses made, exploring the implications of each, drawing out points of controversy and adopting an attitude of critical sympathy to libertarians and marxists, liberals and communitarians. He does this to sustain dialogue, wi thout abandoning his personal convictions or falling into invective or exegesis.